2018
DOI: 10.1002/spe.2565
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of users' privacy concerns by checking of their WhatsApp status

Abstract: Summary WhatsApp Messenger is a popular instant messenger among Iranian users. The WhatsApp status feature provides the possibility of posting desired content without restrictions in terms of type with the capability of being managed by users. Status can be considered as a potential place to express users' feelings, opinions, and thoughts. However, special attention should be paid to the privacy of users and the information published in this manner because access to the content of a user's status by unauthoriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…Burke et al (2011) found that additional features of various social media platforms force users to change how they post and share experiences, resulting in exciting outcomes. Similarly, the status application of WhatsApp has become an emerging social media tool among users these days, where they love to share their leisure time experiences (Malekhosseini et al, 2018). At the same time, other users associated with that loop are attracted to express their feelings by seeing the posts shared on it (News18.com, 2017).…”
Section: Attitudementioning
confidence: 99%
See 3 more Smart Citations
“…Burke et al (2011) found that additional features of various social media platforms force users to change how they post and share experiences, resulting in exciting outcomes. Similarly, the status application of WhatsApp has become an emerging social media tool among users these days, where they love to share their leisure time experiences (Malekhosseini et al, 2018). At the same time, other users associated with that loop are attracted to express their feelings by seeing the posts shared on it (News18.com, 2017).…”
Section: Attitudementioning
confidence: 99%
“…Thus, travel experiences shared on social media are not only about updating an individual or group's leisure time in an expressive way, but also inspiring others, to plan their trips and ultimately support the travel and tourism industry (Kim and Tussyadiah, 2013). The WhatsApp status tool is one of the recent social media platforms these days, which has greatly influenced the posting behavior of travelers (Malekhosseini et al, 2018). Hence, we posit the hypotheses as follows:…”
Section: Self-expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Malekhosseini vd. [15] WhatsApp uygulamasını kullanan kullanıcıların durum ve sesli görüşmelerde bilgi paylaşımındaki kullanıcı gizlilik endişelerini incelemiştir. Sonuçlar yaş, cinsiyet gibi demografik özelliklerine bağlı olmak ile beraber kullanıcıların çoğunluğunda gizlilik kaygısının yüksek olduğunu göstermiştir.…”
Section: Gi̇ri̇ş (Introduction)unclassified